Pengaruh Pengetahuan Pajak, Moral Pajak, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak - Ara Faridah Nur Sausan Aska; Umaimah Umaimah (Universitas Muhammadiyah Gresik, 2022)
This research aims to analyze the the effect of knowledge taxes, tax morale, and sanctions taxation on taxpayer compliance of MSMEs ( Micro, Small, and Medium Enterprises ) in Gresik Regency. This research method uses quantitative descriptive methods and primary data using a questionnaire. The sampling technique uses purposive sampling. Data collection is done by sending questionnaire via broadcasting chat in the form of goolge form. The number of questionnaire processed was 97 questionnaire. Data were analyzed using multiple linier regression analysis. The result of this study indicate that knowledge taxes does not have a significant effect on taxpayer compliance. Whereas tax morale and sanctions taxation has a positive effect on tax compliance.